Holztafelbau mit klebstofffreien Beplankungen - Töws, Dietrich (Karlsruher Berichte zum Ingenieurholzbau / Karlsruher Institut für Technologie, Holzbau und Baukonstruktionen, 2017)
Different glue-free sheathing systems made of solid timber panels are developed within the scope of this dissertation. These systems are then evaluated by their usability as sheathing in shear walls based on common structural design principles. Therefore, different shear connectors are developed and tested in small-scale and large-scale experiments. Using computational model for the timber-frames examined in the experiments shear wall test are simulated and a design proposal is developed.